Technology implementation of TPN on air-to-ground stationary target attack - Shixiong Wang; Jianhua He; Menglong Zhou; Fang Chen (2017 IEEE International Conference on Information and Automation (ICIA), 2017)
The complexity of the modern battlefield and the requirement of accurate and highly efficient attack promotes the further studies of theories and technology implementations for precision strike. Instead of concerning the technical design for the hardware system and its specific actualization, most of previous researches focuses on the traits of the ballistic trajectory and guidance instructions generation in math, leading to those advanced guidance laws' scarce use in practice. Aiming at the mentions above and the character of real-time of improvement of flight control and guidance instructions tracking, a universal implementation method of guidance based on Computer Control System (CCS) is analyzed. Besides, considering of reducing costs of software and technical difficulty, the paper asserts that it is not always necessary to follow the fixed model for some special guidance problems with the specific mechanism. In order to clarify the assertion, we present a novel guidance implementation method on True Proportional Navigation (TPN) in the mode of Air-to-Ground stationary target attack and some comparisons against traditional implementation method on TPN are analyzed. Simulation experiments validate the effectiveness and practicability of the methods we proposed.